Analysis of urban agricultural characteristics along land use gradient in Lagos State, Nigeria (2016)
The paper argued that land use diversity influenced urban agriculture and that understanding the characteristics of each land use type within which urban agriculture is situated will help to identify prospects and challenges confronting urban agriculture. Three hundred questionnaire coupled with personal interviews were used in collecting relevant information and data pertaining to socio-economic and demographic characteristics of urban farmers. Existing land use map of the LGA was updated with the 2010 high-resolution satellite (Quickbird) image of the LGA. Frequencies, cross-tabulation and analysis of variance were used in analysing variations in socio-economic factors across different land use types. The rapid disappearance of urban agricultural sites within the built-up areas is situated within the concept of the survival of the fittest.The results showed that the land use characteristics within which urban agriculture is located moderate its size, rental cost, profit, accessibility to roads network, while it exacts little or no influence on it with regard to distance from markets and water sources. The findings provide new insights into theoretical debates on the role of land use pattern in influencing pertinent factors of urban agriculture in and around cities. It brings to the fore the need to consider the spatial pattern of urban land use in the allocation of space for urban agriculture while emphasising the role of geographical distance in determining urban agricultural outcomes.